1995
DOI: 10.1128/jb.177.7.1734-1741.1995
|View full text |Cite
|
Sign up to set email alerts
|

A lipopolysaccharide-binding domain of the Campylobacter fetus S-layer protein resides within the conserved N terminus of a family of silent and divergent homologs

Abstract: analysis has demonstrated that sapA2 was not expressed in the C. fetus strain from which it was cloned. Further Southern analyses revealed increasing sapA diversity as probes increasingly 3 within the ORF were used. Pulsed-field gel electrophoresis and then Southern blotting with the conserved N-terminal region of the sapA homologs as a probe showed that these genes were tightly clustered on the chromosome. Deletion mutagenesis revealed that the S-layer protein bound serospecifically to the C. fetus lipopolysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 51 publications
(64 reference statements)
5
78
1
1
Order By: Relevance
“…In type A cells, the S-layer protein SapA and its homologs are bound via a conserved N-terminal region of 184 amino acids to the type A LPS. The S-layer protein SapB and its homologs possess a different Nterminal region and recognize cells with type B LPS as a binding site (31,32).…”
Section: Attachment Of S-layer Proteins To the Underlying Cell Envelomentioning
confidence: 99%
“…In type A cells, the S-layer protein SapA and its homologs are bound via a conserved N-terminal region of 184 amino acids to the type A LPS. The S-layer protein SapB and its homologs possess a different Nterminal region and recognize cells with type B LPS as a binding site (31,32).…”
Section: Attachment Of S-layer Proteins To the Underlying Cell Envelomentioning
confidence: 99%
“…As SLPs of the same strain type share the first N-terminal 184 amino acids and then diverge, and because sapA and sapB are identical except for that region, we hypothesized that the binding domain would reside within the N-terminus. Subsequent reattachment studies demonstrating LPS serotype-specific binding with recombinant truncated type A polypeptides (Dworkin et al, 1995b) confirmed the hypothesis.…”
Section: Structure Of Sapa and Its Homologuesmentioning
confidence: 58%
“…Southern hybridization using the 5Ј conserved region to probe genomic DNA from type A C. fetus strains indicates that eight or nine SLP gene cassettes are present in wildtype strains (Tummuru and Blaser, 1992;Fujita et al, 1995). Pulsed-field gel electrophoresis indicates that these cassettes are tightly clustered on a region of less than 93 kb, representing less than 8% of the genome (Dworkin et al, 1995b;Fujita et al, 1995). Beyond the 5Ј conserved region, each SLP gene cassette possesses a variable region that becomes progressively more divergent as the 3Ј end is approached; thus, each homologue encodes a unique SLP due in part to a unique C-terminus (Dworkin et al, 1995b).…”
Section: Structure Of Sapa and Its Homologuesmentioning
confidence: 99%
See 2 more Smart Citations